Passive house / Passivhaus / casa passiva: Metaphorik im europäischen Diskurs des nachhaltigen Bauens - Crestani, Valentina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The paper presents the results of a linguistic analysis of English, German and Italian texts, whose topic is bioarchitecture. The texts are diatopic and diaphasic variable. They belong to the textual genre of web sites, i.e. presentations of institutes and of producers, and they refer to the specific topic of construction of passive houses. Metaphors are analysed in order to find models of conceptualisation in the three languages, showing similarities or differences according to the perspective adopted (whether qualitative or quantitative). The topological similarities between German and English and the differences between German/ English as Germanic languages and Italian as a Romance language are not always to be found in the conceptualisation of metaphors.
Keywords: metaphors; special languages; English; German; Italian; bioarchitecture